Pengaruh Efikasi Diri terhadap Hasil Belajar Siswa Setingkat Madrasah Aliyah - Alif Akbar Maulana; Didit Darmawan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to analyze the influence of self-efficacy on the learning outcomes of students at the Madrasah Aliyah level through literature study. In this study, the authors collected and reviewed various related literature, including journal articles, books, and previous research reports that discussed self-efficacy and its impact on learning. The results of the analysis show that self-efficacy is a person's ability to regulate and carry out the behaviors necessary to achieve certain goals. This happens because they believe that the actions taken will yield the desired results even if in the face of difficulties they have little incentive to act or persevere. These findings indicate the need to increase self-efficacy through training and professional development to improve the learning outcomes of students at the Madrasah Aliyah level. This research is expected to provide insight for policymakers in an effort to improve the quality of education.